Nutrition for female soccer players - Recommendations - Dobrowolski, H.; Karczemna, A.; Wlodarek, D. (Medicina, 2020)
Soccer is one of the most popular sports in the world. As its number of players is increasing, the number of female players is also on the rise. However, there are limited data about how the diets of female soccer players should be designed. Thus, the aim of our work is to deliver concise nutritional recommendations for women practicing this sport. Based on a literature review, we emphasize that individual adjustment of the energy value of the diet is the key factor for the physical performance of female soccer players. Appropriate macronutrient intake makes it possible to achieve the proper energy value of the diet (5-10 g/kg body mass/day carbohydrates; 1.2-1.7 g/kg body mass/day proteins; <30% fats from energy). The micronutrients should be consumed in amounts corresponding to individual values recommended in national standards. Soccer players should pay special attention to the proper consumption of such micronutrients, as well as vitamins such as iron, calcium, and vitamin D. The right amount of fluid intake, consistent with the player`s needs, is crucial in maximizing exercise performance. The diet of a female practicing soccer is usually characterized with low energy values, which increases the risk of various health consequences related to low energy availability. Monitoring the diets of female soccer players is, therefore, necessary